The Graphemes /š/ and /ŋ/ in the Religious Texts of the CODEX CUMANICUS - Göncöl, Csaba (Acta Orientalia Vilnensia, 2017)
The aim of the article is to point out the lack of research on palaeography and orthography of the Codex Cumanicus. The article deals with the use of symbols used to denote the consonants /š/ and /ŋ/ of the religious texts in the “German part” of the manuscript. The texts can be divided into two sections: the first being on folios 61r–63r, while the second on folios 69r–76r and 80r. This difference in use of the symbols may show that there were two different methods of writing consonants, which were foreign to the orthography of Medieval Latin writing, in the above-mentioned two sections of the text. The article stresses the importance of the palaeographical and orthographical analysis on the Codex Cumanicus, in order to be able to draw valid linguistic information from the codex.